Notification of injuries and decision-making of nurses related to HIV/AIDS - Cunha Machado Tavares, Rosangela (2021)
Objective: Reflect on the correlation between the data of health information systems and the decision-making process; Understand the concepts of management and management applied to nursing; Discuss possible implications for decision-making in epidemiological surveillance of HIV/AIDS and the health actions implemented. Method: Integrative Literature Review, conducted between September 2019 and September 2020 in LILACS, BDENF, MEDLINE/PubMed, Scopus and SciELO databases. Main results: Different perceptions were identified regarding the concepts of management and management, noting an influence of the authors' personal conceptions. SINAN showed that it should be one of the main means to support the planning of actions related to HIV/AIDS. In relation to the disease, there was a paradigm shift about population characteristics in the 1980s and in the current decade, reflecting a need to reformulate health policies, so that they are truly effective. General conclusion: Timely and grounded decision-making is paramount in the transcendence of barriers that interfere in the planning of actions related to the presented disease. The need for routine analysis and evaluation of the population, in order to formulate specific health policies and actions for each local reality, it is also possible to make society aware of the constant population transition of the epidemic. Thus strengthening the autonomy, co-responsibility and protagonism of subjects and collectives in the maintenance of their health. Descriptors: Nursing; HIV; Acquired Immunodeficiency Sydrome; Decision Making; Organization and Administration; Health Information Systems; Disease Notification.